Pengaruh Kualitas Pelayanan, Ketepatan Waktu, Dan Kepercayaan Terhadap Kepuasan Pelanggan Shopee Express (Studi Kasus Pada Mahasiswa Di Kota Malang) - Aisyah Ainun Unsiyah; Rois Arifin; Mohammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the relationship between service quality, timeliness and trust in shopee express customer satisfaction. This research uses studies on students in the city of Malang. The data was obtained by distributing questionnaires via Google form to students in the city of Malang who were selected by purposive sampling. Determining the number of samples in this study used the Malhotra formula and the results obtained were 80 respondents. The analytical method used in this study is instrument test (validity test, reliability test), normality test, classical assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test and t test), coefficient of determination test. (Adjusted R2) data processing using the IBM SPSS 24 program. The results of this study indicate that service quality, timeliness and trust have a simultaneous effect on customer satisfaction, service quality has a partial effect on customer satisfaction but not significant, timeliness has a partial effect on customer satisfaction customers but not significant, and trust has a significant effect on customer satisfaction. Keywords: Service Quality, Timeliness, Trust, Customer Satisfaction